2003
DOI: 10.1051/0004-6361:20030163
|View full text |Cite
|
Sign up to set email alerts
|

The Wilson–Bappu effect: A tool to determine stellar distances

Abstract: Abstract. Wilson & Bappu (1957) have shown the existence of a remarkable correlation between the width of the emission in the core of the K line of CaII and the absolute visual magnitude of late-type stars. Here we present a new calibration of the Wilson-Bappu effect based on a sample of 119 nearby stars. We use, for the first time, width measurements based on high resolution and high signal to noise ratio CCD spectra and absolute visual magnitudes from the Hipparcos database. Our primary goal is to investigat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 23 publications
(43 reference statements)
5
36
0
1
Order By: Relevance
“…The emission components with self-reversal in the line cores are clearly seen. By measuring the width of both the H-and the K-lines, following the method of Pace et al (2003), we find an absolute magnitude of M V = 5.4 ± 0.6. Given the spectroscopic effective temperature, the location in the Hertzsprung-Russell diagram indicates that CoRoT-7 is a main sequence star with The self-reversal in the emission cores is shown in the insets.…”
Section: Absolute Magnitude From the Wilson-bappu Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…The emission components with self-reversal in the line cores are clearly seen. By measuring the width of both the H-and the K-lines, following the method of Pace et al (2003), we find an absolute magnitude of M V = 5.4 ± 0.6. Given the spectroscopic effective temperature, the location in the Hertzsprung-Russell diagram indicates that CoRoT-7 is a main sequence star with The self-reversal in the emission cores is shown in the insets.…”
Section: Absolute Magnitude From the Wilson-bappu Effectmentioning
confidence: 99%
“…The calibration of the absolute magnitude is of the form: M V = a log W 0 + b, where W 0 is the width at the zero-level of the emission component, and where the constants a and b also need to be properly calibrated. This is usually done using data from clusters, and we have used the recent calibration of Pace et al (2003), who found a = −18.0 and b = 33.2 with a quoted uncertainty of 0.6 mag on M V .…”
Section: Absolute Magnitude From the Wilson-bappu Effectmentioning
confidence: 99%
“…Numerous explanations were advanced, but Ayres (1979), using scaling laws for the extent and density of the chromosphere, argued that the Wilson-Bappu width is "a stellar barometer, not a tachometer"; i.e., rather than arising from details of chromospheric flows, it is primarily a hydrostatic equilibrium acting in concert with the partial ionization of hydrogen and resonance line cooling to postpone the onset of the sharp thermal instability that gives rise to the corona. Pace et al (2003) suggested that the Wilson-Bappu relationship can be used to infer cluster distances, though it contains too much scatter to be useful for individual stellar distances.…”
Section: Long-term Observations Of Ca II H and Kmentioning
confidence: 99%
“…The practical comparison has been done with the help of the Digital Spectral Classification Atlas by Gray 5 , using high resolution spectra of spectral standards obtained with HARPS, FEROS and UVES. Whenever the emission cores of the Ca ii H&K lines have been present, we have determined the luminosity type from the Wilson-Bappu effect (Wilson & Vainu Bappu 1957), using the calibration by Pace et al (2003). Since many older classifications are done in this way, it is instructive to investigate the differences between this traditional human skill driven task, and a modern automatic classification.…”
Section: Spectral Classificationmentioning
confidence: 99%